2001
DOI: 10.1002/1521-3757(20011001)113:19<3642::aid-ange3642>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Nicht-VSEPR-Strukturen und chemische Bindung in d0-Systemen

Abstract: Martin Kaupp, geboren 1962 in Stuttgart, studierte dort sowie in Cincinnati Chemie. Nach der Diplomarbeit, die er 1989 in Stuttgart bei Hermann Stoll in theoretischer Chemie anfertigte, promovierte er 1992 in Erlangen mit einer quantenchemischen Arbeit bei Paul von Rague Schleyer. Nach einem Aufenthalt am Max-Planck-Institut für Festkörperforschung in Stuttgart bei Hans-Georg von Schnering (1992Schnering ( /1993 setzte er seine Postdoc-Arbeiten 1993/1994 bei Dennis Salahub in MontreÂal fort. 1997 habilitierte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
8

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 395 publications
(302 reference statements)
3
24
0
8
Order By: Relevance
“…Interestingly, for simple hydrides, Landis found that sd n hydrides may be constructed that are surprisingly close to orthogonal 26. However, it remains to be seen whether this observation may be transferred to different types of ligands 27…”
Section: The 3d Shellmentioning
confidence: 99%
“…Interestingly, for simple hydrides, Landis found that sd n hydrides may be constructed that are surprisingly close to orthogonal 26. However, it remains to be seen whether this observation may be transferred to different types of ligands 27…”
Section: The 3d Shellmentioning
confidence: 99%
“…Formally,8 the oxidized Mo VI and reduced Mo IV states of DMSOR may be considered d 0 and d 2 systems, respectively. Under certain circumstances, which have been discussed in detail in a recent review,3 hexacoordinate d 0 or d 2 systems may prefer “non‐VSEPR” structures that are derived from a trigonal prism. While σ bonding involving metal d orbitals favors prismatic structures, π bonding tends to stabilize octahedral metal coordination.…”
Section: Electronic Factors That Control the Preference For Trigonal‐mentioning
confidence: 99%
“…However, dithiolene ligands provide the closest equivalent: When viewed as dianionic dithiolates,8 they may be considered single‐sided π donors. But owing to the partial delocalization of the corresponding π orbital on sulfur into the unsaturated backbone, dithiolenes are particularly weak π donors 3. Indeed, the remarkably poor π‐donor ability could be one of the properties that led to the evolution of the specialized molybdopterin ligands for moco enzymes.…”
Section: Electronic Factors That Control the Preference For Trigonal‐mentioning
confidence: 99%
See 2 more Smart Citations